Zero 00:00 - Yap, Jasmine (2017)
Zero is a visual effects short film by Chew Jia Qi, Sean Lee and Yap Jasmine. On a special day for a few hours, humans are rendered immortal. In the event they do something to cause their death, they would come back to life shortly after. A man takes advantage of this by jumping off from a roof as every time he 'dies', he is brought out of his reality to another world where he can see his dead wife. Time is limited for our protagonist as he attempts to reconnect with her.